Alergia al látex. Avances en el desarrollo de inmunoterapias hipoalergénicas específicas - Escobar A., Alejandro; Guzmán M., María Antonieta; Aguillón G., Juan Carlos (Revista Hospital Clínico Universidad de Chile, 2007)
This review provides a brief update about the strategies that have been developed for the hipoallergenic immunotherapy against latex allergens. Thus, recombinant mutants, chemically modified molecules, anti IgE monoclonal antibodies and T-cell epitope-based peptides have been used. Additionally, recent finds that show the importance of dendritic cells and their potential applicability to latex allergens are included.